PENENTUAN UMUR SIMPAN SIRUP PALA BERDASARKAN PERUBAHAN DERAJAT KEASAMAN pH - Melisa J. Sahambangung; Lady Ch. Lengkey; David Rumambi (Universitas Sam Ratulangi, 2016)
ABSTRACTNorth Sulawesi province known as one of the largest producer of nutmeg crop in Indonesia. North Sulawesi supplies about 75% of the needs of nutmeg world with exports ranging between 1000 to 2000 tons. Processing nutmeg nutmeg syrup is one way of diversification of nutmeg. Small and Medium Industries (SMI)